UPAYA MENINGKATKAN SELF EFFICACY RENDAH TERHADAP PEMILIHAN KARIR DENGAN KONSELING BEHAVIOUR TEKNIK MODELING SIMBOLIK PADA SISWA KELAS X.5 DI SMAN 1 PASAMAN - Mashuda Mashuda (STKIP Pesisir Selatan, 2018)
Abstract Self efficacy is the conviction of within a person of his ability to organize and perform actions in order to achieve the desired results. The problem of low self efficacy towards career selection becomes something serious because it relates to the future and ideals of the students. This research uses individual counseling services behaviour symbolic modeling techniques to improve low self efficacy against career selection in students of Class X.5 in SMAN 1 Pasaman. The purpose of this research is to know the description of low self efficacy level on career selection before and after counseling individual behavioral technique of symbolic modeling. This research is a classroom action research. The research procedure in this research includes planning, action, observation and reflection. This study consists of two cycles with four meetings. The population in this study is all students of Class XII.IPA.3 in SMAN 1 Pasaman, which consists of 34 students. The results showed that 6 students who become research samples have a percentage of self-efficacy level of 52.25% (low category) before obtaining counseling service behavioral technique of symbolic modeling. After obtaining counseling service behavioral technique of symbolic modeling, the average percentage of self efficacy level against career selection becomes 72.25% (high category). There is a difference of self efficacy level to career selection in cycle 1 and cycle 2 after obtaining behavioral counseling technique of symbolic modeling. Overall, self-efficacy against career selection increased 20.5%. Keywords: low self efficacy against career selection, behavioral counseling technique symbolic modeling.